Pengembangan Website Sekolah Sebagai Media Penyampaian Nilai Rapor Siswa (Studi Kasus : SD Negeri 1 Gunung Madu) - Bella Dwi Rahmatulia; Agi Putra Kharisma; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The school website is a set of page that contain school information connected to each other with a link. An example of information that can be shared by the school is the student's rating. Currently, the process of submitting the value of student report card at SD Negeri 1 Gunung Madu is done by meeting parents or guardians directly. However, the process used today is having problems when the COVID-19 pandemic hits as it is now. With the COVID-19 pandemic, zoning systems were implemented in various regions including SD Negeri 1 Gunung Madu. Zoning enforcement causes the process of delivering student report card grades directly can not be carried out. Based on the problems that arise, the school website is created that aims to convey and manage the value of student reports. The development of the school website at SD Negeri 1 Gunung Madu using waterfall method resulted in 46 functional needs for administration, 29 functional needs for homeroom parents and 4 functional needs for students after passing 2 iterations. The implementation of this school website uses the AngularJs framework and the PHP framework SLIM. Functional testing includes unit testing and integration testing. Both unit testing and integration testing successfully obtained passed status. In addition, validation tests out of a total of 80 test cases get 100% valid results. Non-functional testing includes compatibility testing using website testing tool SortSite and usability testing using System Usability Scale (SUS).